Pengaruh Model Kooperatif Tipe Make A Match Berbantuan Wordwall Terhadap Hasil Belajar Kelas V Sekolah Dasar - Devi Rusdyani; Reinita Reinita (Universitas Negeri Padang, 2023)
This research was conducted to determine how much influence the application of the Make a Match model assisted by the Wordwall application on the learning outcomes of students in grade V SD Cluster I Pauh District, Padang. This is quantitative research with a quasi-experimental design. The samples were SDN 04 Pisang (experimental) and SDN 08 Pisang (control) were selected using a simple random sampling technique. The research instrument used is a test in the form of multiple-choice questions that have been validated and analyzed with validity, reliability, differentiating power, and difficulty level. The data analysis techniques used are a t-test that has met the prerequisite test (normality and homogeneity test) and an n-gain score. Based on the post-test results, the average of the experimental group (80,07) >the control group (69,83). The results of the analysis using the t-test: tcount = 3.3923 > ttable = 2.0106, so that Ha is accepted and H0 is rejected. The results of the n-gain score test obtained an average increase in the experimental group = 33.42% > control group =18.20%. It can be concluded that there is an influence of the application of the Make a Match model assisted by the Wordwall application on student learning outcomes